2019
DOI: 10.3389/fneur.2019.00658
|View full text |Cite
|
Sign up to set email alerts
|

Patency of Posterior Circulation Branches Covered by Flow Diverter Device: A Hemodynamic Study

Abstract: Objective: Flow diverter devices are increasingly used in the treatment of posterior circulation aneurysms, sometimes necessarily involving ostia of side branches and perforators. The aim of this study was to identify the hemodynamic influence of flow diverters on side branches and perforators of the posterior circulation. Methods: We performed a retrospective study of consecutive patients treated by a flow diverter device for posterior circulation aneurysms with anterior inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
3
4
0
Order By: Relevance
“…Levitt et al ( 18 ) reported that all the PICA maintained patency in six cases with vertebral artery aneurysms involving PICA treated by flow diverting stent. Similar results were reported by Adeeb et al ( 19 ) and Wu et al ( 20 ). These data suggested that the PICA can be effectively and safely preserved when using PED in treatment of these lesions.…”
Section: Discussionsupporting
confidence: 91%
“…Levitt et al ( 18 ) reported that all the PICA maintained patency in six cases with vertebral artery aneurysms involving PICA treated by flow diverting stent. Similar results were reported by Adeeb et al ( 19 ) and Wu et al ( 20 ). These data suggested that the PICA can be effectively and safely preserved when using PED in treatment of these lesions.…”
Section: Discussionsupporting
confidence: 91%
“…A recent meta-analysis by Liang et al that investigated the PED in posterior circulation aneurysms included 12 studies with 358 patients with 365 aneurysms. 35 They reported a pooled long-term aneurysmal occlusion rate of 82% (95% CI, 73-90) and pooled procedure-related complication rate of 18% (95% CI, [14][15][16][17][18][19][20][21][22]. Despite differences in inclusion criteria, the aneurysmal occlusion rates in these studies are in line with our findings.…”
Section: Discussionsupporting
confidence: 83%
“…13 Moreover, their safety has not been well-defined and many studies have shown that posterior circulation aneurysms are associated with a higher rate of ischemic complications due to occlusion of perforators. 14 We performed this systematic literature review to assess the efficacy and safety of FDs in the management of posterior circulation cerebral aneurysms and compare their efficacy between anterior and posterior circulation aneurysms.…”
Section: Introductionmentioning
confidence: 99%
“…Five of these LGVBA patients received coil-assisted embolization and all had favorable outcomes. Our results here are similar; 19 (90%) of the 21 LGVBA patients achieved favorable outcomes, nine patients in the PED with adjunctive coils group (100%) all had favorable outcomes, 10 patients in PED group (83%) had favorable outcomes. Although there was no statistical difference between the two groups in clinical and imaging follow-up, our results indicated that PED combined with coils did not increase perioperative or longterm complications.…”
Section: Discussionsupporting
confidence: 76%